Azobenzene-based liquid crystal dimers and the twist-bend nematic phase. Issue 12 (21st October 2017) - Paterson, Daniel A.; Walker, Rebecca; Abberley, Jordan P.; Forestier, Jérémy; Harrison, William T. A.; Storey, John M. D.; Pociecha, Damian; Gorecka, Ewa; Imrie, Corrie T.
ABSTRACT: The synthesis and characterisation of two new sets of non-symmetric liquid crystal dimers is reported, the 1-(4-substitutedazobenzene-4′-yloxy)-6-(4-cyanobiphenyl-4′-yl)hexanes (CB6OABX) and 1-(4-substitutedazobenzene-4′-yloxy)-6-(4-cyanobiphenyl-4′-yloxy)pentanes (CBO5OABX). The terminal substituents are methyl, methoxy, butyl, butyloxy, nitrile and nitro. All the CB6OABX dimers exhibit twist-bend nematic (NTB ) and nematic (N) phases. The CBO5OABX dimers also all show an N phase but only the butyl and butyloxy homologues exhibit the NTB phase. The transitional behaviour of the non-symmetric dimers is compared to that of the corresponding symmetric dimers, the 1, 5-bis(4-substitutedazobenzene-4′-yloxy)pentanes (XABO5OABX) and either 1, 7-bis(4-cyanobiphenyl-4′-yl)heptane or 1, 5-bis(4-cyanobiphenyl-4′-yloxy)pentane. The XABO5OABX dimers all show a nematic phase and in addition, the butyl homologue exhibits a smectic A phase. The difference in transitional behaviour between the CB6OABX and CBO5OABX dimers is attributed to the difference in their molecular shapes arising from different bond angles between the para axis of the cyanobiphenyl unit and the first bond in the spacer. Specifically, the all- trans conformation of a CBO5OABX dimer is more linear than that of the corresponding CB6OABX dimer. Differences within each set of dimers are attributed to changes in the average molecular shape and the strength of the mixed mesogen interaction on varying the terminal group. Crystal structures are reported for CB6OABOMe, CBO5OABNO2 and MeOABO5OABOMe. Graphical Abstract: